Assessment of suitable variety of marigold (Tagetes erecta) for northern dry zone condition (Current Horticulture, 2024)
This field experiment was laid out by adopting  F test at farmers’ fields of marigold (Tagetes  species Linn.) at Mutkod and Kellur village of  Jewargi taluk during 2018-19. Totally 3 treatments  were considered by three different varieties, Arka  Agni and Arka Bangara 2 from IIHR, Bengaluru and  local variety from Jewargi. The mean value of plant  height was highest in Arka Agni (40.16 cm), followed  by local variety (35.6 cm) Arka Bangara 2(33.6 cm). The  variation in plant height due to genotypic differences  in phenotypic expression of plant height is due to  genotype-environmental interaction effects on plant  height.
Keywords: genotypes showed; environmental factors